2020
DOI: 10.1002/bab.2017
|View full text |Cite
|
Sign up to set email alerts
|

Secondary metabolite contents and antimicrobial activity of leaf extracts reveal genetic variability of Vernonia amygdalina and Vernonia calvoana morphotypes

Abstract: Vernonia species (Asteraceae) are indigenous medicinal and food leaf vegetables commonly consumed in some African countries like Cameroon where they constitute a staple dish called “ndolé.” Previous studies have demonstrated the nutritional importance of Vernonia, but there is little knowledge of their agronomic value and genetic potentials. Wide genetic variability in the genus has been established earlier through the study of its pollen. However, to the best of our understanding, no such study has been under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 20 publications
1
8
0
Order By: Relevance
“…Similarly, ethanolic extracts of L. vulgare and V. amygdalina showed a broad-spectrum antimicrobial activity against all the tested pathogens. This could be ascribed to the richness of these extracts in phytochemicals such as saponins, sesquiterpenes, flavonoids, steroid glycosides, and lactones [20] for which recent studies reported its antibacterial activity [21]. Amongst leaves extracts, those derived from M. oleifera were more actives against the bacterial strains E. coli ATCC 25922 and S. aureus ATCC 6538 while extract from L. vulgare leaves was more active against C. albicans ATCC 10231.…”
Section: Inhibition Zone Of Extract Against Tested Bacteriamentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, ethanolic extracts of L. vulgare and V. amygdalina showed a broad-spectrum antimicrobial activity against all the tested pathogens. This could be ascribed to the richness of these extracts in phytochemicals such as saponins, sesquiterpenes, flavonoids, steroid glycosides, and lactones [20] for which recent studies reported its antibacterial activity [21]. Amongst leaves extracts, those derived from M. oleifera were more actives against the bacterial strains E. coli ATCC 25922 and S. aureus ATCC 6538 while extract from L. vulgare leaves was more active against C. albicans ATCC 10231.…”
Section: Inhibition Zone Of Extract Against Tested Bacteriamentioning
confidence: 99%
“…It has also been reported to have antioxidant, anti-inflammatory, antitumor, antimicrobial, hepatoprotective and anti-arthritic properties [14][15][16]. V. amygdalina (known in Cameroon under the popular name of Ndolè) have been reported to have anticancer and antitumor activity [17,18]; antihepatotoxic activity [19]; hypoglycemic activity [20]; antibacterial activity [21]; anti-inflammatory [22] as well as antioxidant property [23]. Moreover, C. citratus (lemongrass) is widely used as a tea and is rich in minerals, vitamins, macronutrients (including carbohydrate, protein, and small amounts of fat) and its leaves are a good source of various bioactive compounds such as alkaloids, terpenoids, flavonoids, phenols, saponins and tannins that confer C. citratus leaves pharmacological properties such as anti-cancer, antihypertensive, anti-mutagenicity, anti-diabetic, antioxidant, anxiolytic, anti-nociceptive and anti-fungal [24].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Cameroon, V. amygdalina is known under the name of Ndolè and is included in the composition of the national popular dish which bears the same name. The presence of polyphenols, vitamins and mineral salts make the plant useful in human diets [25,26]. V. amygdalina is very rich in phytochemicals such as saponins, sesquiterpenes, flavonoids, and steroid glycosides (vernosides), lactones [26] and several studies reported that it has anticancer and antitumor activity [27,28]; antihepatotoxic activity [29]; hypoglycemic activity [26]; antibacterial activity [30]; anti-inflammatory [31] as well as antioxidant property [32].…”
mentioning
confidence: 99%
“…It has also been reported to have Antioxidant, antiinflammatory, antitumor, antimicrobial, hepatoprotective and anti-arthritic properties (Ray et al, 2015; Arulselvan et al, 2016;Saleem et al, 2020). V. amygdalina (known in Cameroon under the popular name of Ndolè) have been reported to have anticancer and antitumor activity (Hasibuan et al, 2020;Joseph et al, 2020); antihepatotoxic activity (Yedjou et al, 2018); hypoglycemic activity (Dumas et al, 2020); antibacterial activity (Egbuonu and Amadi, 2021); anti-inflammatory (Wang et al, 2020) as well as antioxidant property (Alara and Abdurahman, 2021). Moreover, C. citratus (lemongrass) is widely used as a tea and is rich in minerals, vitamins, macronutrients (including carbohydrate, protein, and small amounts of fat) and its leaves are a good source of various bioactive compounds such as alkaloids, terpenoids, flavonoids, phenols, saponins and tannins that confer C. citratus leaves pharmacological properties such as anti-cancer, antihypertensive, anti-mutagenicity, anti-diabetic, anti-oxidant, anxiolytic, anti-nociceptive and anti-fungal (Muala et al ., 2021).…”
mentioning
confidence: 99%